2018
DOI: 10.1002/solr.201800211
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Graphdiyne‐ZnO Nanocomposite Material and Application in Polymer Solar Cells

Abstract: Graphdiyne-ZnO (GDZO) composite material is prepared via a simple method and studied in detail for the first time. The transmission electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) analyses confirm the formation of an adduct between GD and ZnO. Then the interaction between ZnO and GD is further investigated by first-principles calculations. It is found that the Zn and O atom can coordinate bonding with GD, thus forming the C─Zn bond and C─O bond, respectively. Polymer solar ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…An appreciable increase in the semicircle diameters (Figure g) indicates a better interfacial contact between perovskite and ClGD‐PCBM film compared with pure PCBM, resulting in the decrease in charge recombination at the interface and the improvement of FF . Corresponding bode EIS spectra (Figure S5, Supporting Information) demonstrate that ClGD‐PCBM ETLs have a higher electron density and faster electron transfer (1.59 μs) compared with PCBM ETLs (2.57 μs), which further supports the results of electron mobility and PL . We proposed that the faster electron transfer reduces charge accumulations between the perovskite active layer and electrode, leading to a decrease in J – V hysteresis .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…An appreciable increase in the semicircle diameters (Figure g) indicates a better interfacial contact between perovskite and ClGD‐PCBM film compared with pure PCBM, resulting in the decrease in charge recombination at the interface and the improvement of FF . Corresponding bode EIS spectra (Figure S5, Supporting Information) demonstrate that ClGD‐PCBM ETLs have a higher electron density and faster electron transfer (1.59 μs) compared with PCBM ETLs (2.57 μs), which further supports the results of electron mobility and PL . We proposed that the faster electron transfer reduces charge accumulations between the perovskite active layer and electrode, leading to a decrease in J – V hysteresis .…”
Section: Resultssupporting
confidence: 73%
“…It is shifted to 1434.3 cm −1 upon formation of the ClGD‐PCBM. Such a shift implies the formation of the interaction between C 60 (main body of PCBM) and ClGD . Moreover, in comparison with unbonded ClGD, the vibration of acetylenic linkages (—C—C≡C—C—) of ClGD‐PCBM at around 2191.9 cm −1 was weakened, which may be attributed to the decline of the energy of the corresponding phonon modes due to the existence of π–π interaction between ClGD and PCBM .…”
Section: Resultsmentioning
confidence: 98%
“…The effect of the dosed NdCl 3 on nonradiative recombination was also checked by the dark current curves and electrochemical impedance spectroscopy (EIS) of PvSCs. The reverse saturation current density ( J 0 ) was calculated , as 2.89 × 10 –5 mA/cm 2 for the c-SnO x -based device and 1.43 × 10 –6 mA/cm 2 for the SnO x :NdCl 3 -based device, respectively (see Figure S13a). As is known, the lower J 0 indicated less nonradiative recombination, which would lead to an improvement in V OC .…”
Section: Resultsmentioning
confidence: 99%
“…GDY has been applied in polymer solar cells, , perovskite solar cells, fuel cells, and photocatalysis fields. , Xiao et al reported perovskite solar cells using GDY as a dopant in the hole-transporting material (HTM) layer of poly­(3-hexylthiophene) (P3HT) (as shown in Figure A) . The results of Raman spectra and UV electron spectra exhibited that between the GDY particles and P3HT a strong π–π stacking interaction is observed, which is beneficial for hole transport and improved performance.…”
Section: Applications Of Xenes and Their Heterostructuresmentioning
confidence: 99%